Effect of Yellow Sweet Potato Substitution and Egg Yolk Amount in Making Wet Noodles: - - Paramuji, Muji; Wanbahroni Jiwar Barus; Miranti; Aprilawati Sitompul; Muhammad Nuh; Eka Ayutiningsih (Talenta Publisher, 2022)
Most of the noodles are made from wheat flour, for countries that do not produce wheat this is a problem because the need for wheat must be imported and generates a large amount of foreign exchange. This situation resulted in research involving the use of non-wheat flour or mixing wheat flour with other flour to produce noodles. This study aims to determine the effect of the substitution of wheat flour with yellow sweet potato and the amount of egg yolk in the manufacture of wet noodles. The study used a factorial completely randomized design (CRD), which consisted of two factors, namely: substitution of wheat flour with yellow sweet potato with the code